Survival outcome of neonates admitted at government and private neonatal intensive care units of Allahabad, India - Dwivedi, Kriti; Prakash, Shiv; Parveen, Khurshid; Shaikh, Shama (International Journal Of Community Medicine And Public Health, 2017)
Background: The early neonatal period (birth to 7 days of life) is the most critical period of life. Usually, the lower the infant mortality, the greater of it is concentrated in neonatal period. The present study was carried out with the objectives to study the profile of sick neonates & compare their survival outcome admitted in Government and Private NICUs of Allahabad. Methods: The cross-sectional study was conducted in the NICUs of Government & Private sector of comparable admission rates in Allahabad. The study was time bound conducted from September 2015-August 2016. The data were collected from the medical records of the admitted neonates. Results: There were a total of 1442 neonates admitted during the given time frame in both the Government and Private NICUs and 1409 were included in the study. The Government NICU had 63.21% admissions within 24 hour of birth more than Private NICUs (55.03%). The Private NICU had 36.58% neonates admitted within 1-7 day while Government sector had 29.88%. The Government NICU had 69.01% rural patients while Private NICU had 67.98% urban patients. The Government NICU received 57.63% outborn babies while Private NICU had more inborn babies (67.22%). The profile of sick neonates according to age at the time of admission, mode of admission and community in Government and Private NICUs differed significantly (p<0.05) while gender, gestational age and weight were not significantly different. Conclusions: The Government NICU had a survival outcome of 70.91% while Private NICU had 86.73% which was statistically significant.